Individualism-collectivism and interpersonal memory guidance of attention - He, X; Sebanz, N; Sui, J; Humphreys, G (Academic Press Inc., 2014)
Recently it has been shown that the allocation of attention by a participant in a visual search task can be affected by memory items that have to be maintained by a co-actor, when similar tasks are jointly engaged by dyads (He, Lever, and Humphreys, 2011). In the present study we examined the contribution of individualism-collectivism to this 'interpersonal memory guidance' effect. Actors performed visual search while a preview image was either held by the critical participant, held by a co-actor or was irrelevant to either participant. Attention during search was attracted to stimuli that matched the contents of the co-actor's memory. This interpersonal effect correlated with the collectivism scores, and was enhanced by priming with a collectivistic scenario. The dimensions of individualism, however, did not contribute to performance. These data suggest that collectivism, but not individualism, modulates interpersonal influences on memory and attention in joint action.© 2014.